Structure and thermal expansion of the low-temperature phase of SF 6 - Isakina, A. P.; Prokhvatilov, A. I.; Rodriguez-Carvajal, J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
Powder x-ray and neutron diffraction studies of the crystalline structure, lattice parameters and thermal expansion coefficients of sulphur hexafluoride SF6 are performed in the temperature range1.64√110 K. It is shown that the low-temperature phase (at T < 94.3 K) is monoclinic, space group C 2/m (C2h3 ) with Z=6 in which 1/3 of molecules SF6 occupy the positions of higher symmetry (2/m) and 2/3 of molecules ≈ lower one (m). As follows from the analysis of obtained structural results, anavailability of two types of molecular local symmetry positions is responsible for the anisotropic character of molecular rotation, peculiarities on the temperature dependences of structural and thermo-dynamicproperties of SF6 crystals at low-temperature phase, especially near Tc of orientational phase transition. It is carried out a detail comparison the present results with the known literature data.